The degree of labor pain at the time of epidural analgesia in nulliparous women influences the obstetric outcome - Woo, Jae Hee (Korean J Anesthesiol, 2015)
BACKGROUND: The increased pain at the latent phase can be associated with dysfunctional labor as well as increases in cesarean delivery frequency. We aimed to research the effect of the degree of pain at the time of epidural analgesia on the entire labor process including the mode of delivery. METHODS: We performed epidural analgesia to 102 nulliparous women on patients' request. We divided the group into three based on NRS (numeric rating scale) at the moment of epidural analgesia; mild pain, NRS 1-4; moderate pain, NRS 5-7; severe pain, NRS 8-10. The primary outcome was the mode of delivery (normal labor or cesarean delivery). RESULTS: There were significant differences in the mode of delivery among groups. Patients with severe labor pain had a significantly higher cesarean delivery compared to patients with moderate labor pain (P = 0.006). The duration of the first and second stage of labor, fetal heart rate, use of oxytocin and premature rupture of membranes had no differences in the three groups. CONCLUSIONS: Our research showed that the degree of pain at the time of epidural analgesia request might influence the rate of cesarean delivery. Further research would be necessary for clarifying the mechanism that the augmentation of pain affects the mode of delivery.